2002
DOI: 10.1080/13556210220139523
|View full text |Cite
|
Sign up to set email alerts
|

Green tea as a potent antioxidant in alcohol intoxication

Abstract: Ethanol oxidation to acetaldehyde and next to acetate is accompanied by free radical generation. Free radicals can affect cell integrity when antioxidant mechanisms are no longer able to cope with the free radical generation observed in ethanol intoxication. Natural antioxidants are particularly useful in such a situation. The present study was designed to investigate the efficacy of green tea as a source of water-soluble antioxidants (catechins) on the liver and blood serum antioxidative potential of rats chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 46 publications
2
28
0
1
Order By: Relevance
“…48,54,55) Indeed, it has been suggested that drugs such as EGCG that have antioxidant capacities and radical scavenging properties might be useful in treating alcohol-induced liver damage. 50,56,57) However, in contrast to its antioxidative activity, some experiments in vitro indicate that EGCG produces reactive oxygen species. For example, EGCG promotes apoptosis and has bactericidal activity, which is attributed to its ability to reduce O 2 to yield H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…48,54,55) Indeed, it has been suggested that drugs such as EGCG that have antioxidant capacities and radical scavenging properties might be useful in treating alcohol-induced liver damage. 50,56,57) However, in contrast to its antioxidative activity, some experiments in vitro indicate that EGCG produces reactive oxygen species. For example, EGCG promotes apoptosis and has bactericidal activity, which is attributed to its ability to reduce O 2 to yield H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that the swimming training, supplementation, and their combined effects are beneficial in curtailing lipid peroxidation in the brain regions of both the age groups. Studies by Skryzdlewska et al showed that the polyphenols from green tea helps in antioxidative capacity of the brain tissue and in lowering the level of lipid peroxidation products [44]. Devi and Kiran reported that the integration of vitamin E and exercise may act as useful neuroprotector against age-related decline in the antioxidant enzymes and increased lipid peroxidation [10].…”
Section: Discussionmentioning
confidence: 99%
“…This protection may be attributed to phosphorylation and activation of endothelial nitric oxide syntheses in endothelial cells through modulation of protein kinase C. A signaling pathways by green tea resulting in endothelial dependant vasorelaxtion (Lorenz et al, 2004). So in our present study demonstrate that, the activity of the MDA in malathion exposed group increased 2 fold compared with that of the control one, these finding is in accordance with Gultekin et al (2001) who reported that MDA values increased with increasing organophosphorous compounds concentration and incubation period (Ranjbar et al, 2005), may be due to Lipid peroxidation was seen in erythrocytes and liver of rats when exposed to malathion orally for 4 weeks at dose of 5,25 and 75 mg/Kg, respectively (Abdollahi et al, 2004) While in groups treated by malathion plus vitamine c or malathion plus green tea there were a significant decrease in MDA values in comparison with malathion group may be due to The protective effect of vitamin c over malathion toxicity is likely to be mediated via the inhibition of free radical generation and enhancement of free radical scavenging activity (Suna et al, 2010) and Green tea prevents the loss of lipophilic antioxidant α-tocopherol by repairing tocopheryl radicals and protection of the hydrophilic antioxidant ascorbate (Skryzdlewska et al, 2002). Therefore, it may decrease the concentration of lipid free radicals and terminate initiation and propagation of lipid peroxidation (Guo et al, 1999).…”
Section: Discussionmentioning
confidence: 99%